Mapping the Changjiang Diluted Water in the East China Sea during summer over a 10-year period using GOCI satellite sensor data - Son, Young Baek; Choi, Jong-Kuk (Frontiers in Marine Science, 2022)
The Changjiang River loads freshwater into the East China Sea (ECS) and the Yellow Sea (YS). A low-salinity plume known as Changjiang Diluted Water (CDW) is formed by mixing with saline ambient waters; it disperses toward Jeju Island and the East/Japan Sea due to the dominant southerly wind and tide during summer. To map the offshore surface CDW in the ECS, a proxy was developed using surface water beam attenuation (c) and salinity from 18 annual summer cruises matched with synchronous Geostationary Ocean Color Imager (GOCI) satellite data. We followed a two-step empirical approach. First, a relationship between in situ salinity and c was obtained from hydrographic cruises (1998, 2003–2018, and 2021). Second, in situ c was matched with GOCI remote-sensing reflectance (Rrs) band ratios of all available blue-to-green wavelengths (2011–2018). Finally, satellite-derived surface salinity was determined directly by combining the two empirical relationships, providing a robust estimate over a range of salinities (22–34 psu). Our algorithm was then compared and validated with five previous satellite-derived salinity algorithms based on colored dissolved organic matter and particle concentrations. In the first step, surface salinity was matched and well correlated with c using an 18-year full conductivity–temperature–depth (CTD) dataset (N = 1,345, R2 = 0.93). In the second step, c was synchronously matched and well correlated with GOCI Rrs band ratios using an 8-year summer CTD dataset (N = 391, R2 = 0.93). The satellite-derived surface salinity based on the GOCI was compared with five other approaches and validated using an 8-year summer CTD dataset (2011–2018, N = 707, RMSE = 0.43, bias = 0.053, mean ratio = 1.002). We mapped satellite-derived surface salinity using monthly GOCI images during the summer from 2011 to 2020. The spatial patterns of the CDW were connected to the Changjiang River mouth and extended to the east–northeast during summer. Saline water was confined to the warm current and the upper slope in the eastern part of the study area. Anomalous dispersion of the CDW occurred in August 2016, 2017, and 2020, and limited dispersion occurred in August 2014 and 2019.